Thermal regulation of partially floating photovoltaics for enhanced electricity production: A modeling and experimental analysis. (October 2022) - Elminshawy, Nabil A.S.; Osama, Amr; Naeim, Noha; Elbaksawi, Osama; Marco Tina, Giuseppe
Abstract: The thermal regulation of the floating photovoltaic (FPV) system increases its electrical potential. In this study, a partially floating photovoltaic (PFPV) system was examined by submerging a portion of the FPV module to realize excess heat release. An appropriate MATLAB/Simulink model was constructed for a comparative study of three FPV configurations to reveal the electrical benefits of the PFPV system. The proposed model was validated via experimental work under actual outdoor conditions, which revealed well-matched results. According to the modeling findings, submerging half of the PV module in the water body realized a temperature of 29.71 °C, a temperature drop of 28.24 % compared with that of the typical FPV system (41.40 °C). The electrical power generated increased by 5.57 % when 25 % of the active area of the PFPV system was submerged. Furthermore, the findings revealed that the electrical efficiency of the PFPV module reached 15.72 % when 25 % of the PFPV system was submerged, achieving an efficiency improvement of 3.95 % compared with the conventional FPV system. The superiority of the electrical performance of the PFPV system with a submerged area of 25 % in the modeling and its experimental validation ensure the proposed concept validity.